Rancang Bangun Sistem Informasi Manajemen Aset Berbasis Web untuk Menghitung Penyusutan Fiskal - Nasrul Nasrul; Henry Saptono; Edi Wibowo; Amalia Amalia (Jurnal Informatika Terpadu, 2024)
Effective asset management is a critical component in maintaining the financial and operational stability of an institution. At STT Terpadu Nurul Fikri, asset management still relies on manual processes, resulting in inefficiency and increased risk of errors. One crucial aspect of asset management is fiscal depreciation calculation, a process that considers the reduction in asset value over its useful life for fiscal or taxation purposes. Despite its importance, the fiscal depreciation calculation process at STT Terpadu Nurul Fikri still depends on manual Excel spreadsheet usage. This approach is prone to errors, difficult to track, and time-consuming. This research aims to design and develop a web-based asset management information system using the Laravel Framework, employing the Extreme Programming (XP) software development methodology. XP provides flexibility for developers to adapt to changing needs and ensures the quality of the resulting product. The conclusion of this research is that by employing the XP approach and leveraging the Laravel Framework, the development of this system is expected to provide an effective solution to the challenges faced in asset management. This will ease the management of assets for STT Terpadu Nurul Fikri and simplify the fiscal depreciation calculation process for its assets.